Genetically encoded fluorescent unnatural amino acids and FRET probes for detecting deubiquitinase activities. Issue 73 (24th August 2022) - Li, Manjia; Wang, Feifei; Yan, Long; Lu, Minghao; Zhang, Yuqing; Peng, Tao
Abstract : 7-Aminocoumarin-derived fluorescent unnatural amino acids are site-specifically incorporated into proteins and utilized to develop fully genetically encoded FRET probes for deubiquitinases. Abstract : Herein we present the genetic encoding of 7-aminocoumarin-based lysine derivatives, ACouK and AFCouK, into proteins in both bacterial and mammalian cells and the characterization of FRET pairs comprising ACouK or AFCouK as the donor and GFP as the acceptor. We further report the application of the FRET pairs to construct fully genetically encoded ratiometric probes for detecting deubiquitinases and screening for inhibitors.